The link between Work Motivation and Organizational Commitment – Differences between Central and Local Authority Employees - Sagituly, Gaziz; Guo, Junhua (The journal of contemporary issues in business and government, 2021)
Despite the fact that both the central and local executive bodies are part of the Kazakhstani public administration system, its working conditions, salaries, social allowances and employment relationships are different. Therefore, it can be assumed that civil servants’ attitudes toward their job and organizations, and relationships between them, are different. This paper investigates the motivation-commitment link with respect to differences between central and local authorities’ employees, with a number of goals: to determine levels of motivation and commitment vary the employment place; to identify the main motivation factors that might influence each dimension of organizational commitment. A sample of 1205 civil servants completed standardized questionnaires. The results show significant relationships between motivation and organizational commitment. Results also confirmed the hypothesized relationship differences: Intrinsic and extrinsic motivations are more strongly related to the continuance and normative commitment for central authority employees than for local authority ones. In turn, when both motivational factors increase, local authority employees have a stronger affective commitment than do central authority’s employees.